Food Poisoning Risk Analysis in the Free Nutritional Meal Program in Educational Units Based on the Risk Governance Framework: Analisis Risiko Keracunan Makanan Pada Program Makan Bergizi Gratis di Satuan Pendidikan Berbasis Risk Governance Framework - Suci Fitrah Syari; Henny Sulistiawati; Nia Heriani (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2026)
The Free Nutritious Meals (MBG) Program is a national strategic policy to improve the quality of human resources, but its implementation in educational institutions presents food safety risks, particularly food poisoning. Several cases of mass poisoning have occurred, demonstrating that the MBG problem is not merely technical in nature, but rather reflects systemic risks influenced by the interaction between food hazards, student exposure levels, school capacity vulnerabilities, and weaknesses in public policy governance. This study aims to analyze the risk of food poisoning in the MBG program in educational institutions and to map program vulnerabilities in the risk analysis model. The research method used is qualitative based on the Risk governance framework by the International Risk governance Coucil. The analysis is conducted through the stages of pre-risk assessment, risk assessment, risk evaluation, risk management, and risk communication. The results show that the risk of food poisoning in the MBG is still managed reactively, with weak early detection, fragmented roles between actors, limited integration of technical and social data, and low transparency and public participation. Based on these findings, this study produces a Food Poisoning Risk Analysis Model for the MBG Program that is analytical and contextual, based on educational institutions. This model serves as a risk mapping tool to identify critical points of program vulnerability and provides an analytical basis for strengthening food security governance and developing risk-based and sustainable policy mitigation strategies.